2009
DOI: 10.1080/11038120903125101
|View full text |Cite
|
Sign up to set email alerts
|

Parents' and therapists' perceptions of the content of the Manual Ability Classification System, MACS

Abstract: The Manual Ability Classification System (MACS) is a newly developed five-level classification that describes how children with cerebral palsy (CP) use their hands when handling objects in daily life. Since the MACS level is to be determined by asking the parents or someone else who knows the child well, it is important that the classification is meaningful and easy to understand. The aim of this study was to investigate the content validity based on parents' and therapists' descriptions of the children's abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…17 The MACS is also recommended by this review as a suitable tool for classifying upper limb function as it has evidence of interrater reliability 10,30,31 and content validity. 10,11 However, Plasschaert et al 31 advocated cautious use of the system in children with CP under the age of 2 years because of lower reliability values compared with children aged between 2 and 5 years (j=0.55 and 0.67 respectively). Moreover, the studies that evaluated the validity of the MACS 10,11 only included children between 8 and 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The MACS is also recommended by this review as a suitable tool for classifying upper limb function as it has evidence of interrater reliability 10,30,31 and content validity. 10,11 However, Plasschaert et al 31 advocated cautious use of the system in children with CP under the age of 2 years because of lower reliability values compared with children aged between 2 and 5 years (j=0.55 and 0.67 respectively). Moreover, the studies that evaluated the validity of the MACS 10,11 only included children between 8 and 12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, Plasschaert et al 31 advocated cautious use of the system in children with CP under the age of 2 years because of lower reliability values compared with children aged between 2 and 5 years (j=0.55 and 0.67 respectively). Moreover, the studies that evaluated the validity of the MACS 10,11 only included children between 8 and 12 years of age. As a result it is not clear whether it is possible to evaluate validly manual ability using the MACS in younger children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its content validity has been established through focus groups, literature review, and detailed interviews. 7,11 Reliability is supported by ICC values greater than 0.75 (regarded as "excellent reliability") 23 for children between 4 and 18 years of age and adults aged between 18 and 24 years, although it was not originally designed for the adult population. Substantial agreement 24 has been obtained for classification of children between 2 and 5 years of age but only moderate agreement 21 for children under 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…7 Content validity was further explored by interviews with parents and therapists. 11 Findings in these validity studies demonstrated that the descriptions of each level and the difference between the levels of the MACS are clear and meaningful in describing the performance of manual tasks of children with CP. In this scoping review, 9 publications were identified, which focused on reliability of the MACS.…”
Section: Number Of Publicationsmentioning
confidence: 97%